Incidence and Clinical Significance of De Novo Donor Specific Antibodies after Kidney Transplantation. (21st November 2013) - Lionaki, Sophia; Panagiotellis, Konstantinos; Iniotaki, Aliki; Boletis, John N.
Abstract : Kidney transplantation has evolved over more than half a century and remarkable progress has been made in patient and graft outcomes. Despite these advances, chronic allograft dysfunction remains a major problem. Among other reasons, de novo formation of antibodies against donor human leukocyte antigens has been recognized as one of the major risk factors for reduced allograft survival. The type of treatment in the presence of donor specific antibodies (DSA) posttransplantation is largely related to the clinical syndrome the patient presents with at the time of detection. There is no consensus regarding the treatment of stable renal transplant recipients with circulating de novo DSA. On the contrast, in acute or chronic allograft dysfunction transplant centers use various protocols in order to reduce the amount of circulating DSA and achieve long-term graft survival. These protocols include removal of the antibodies by plasmapheresis, intravenous administration of immunoglobulin, or depletion of B cells with anti-CD20 monoclonal antibodies along with tacrolimus and mycophenolate mofetil. This review aims at the comprehension of the clinical correlations of de novo DSA in kidney transplant recipients, assessment of their prognostic value, and providing insights into the management of these patients.